Specific in aggregation of characteristics describing internal quality of IS specification language - Gasperovič, Jelena; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2005)
The paper discusses how to construct taxonomy of characteristics describing internal quality of IS specification language and aggregation techniques that ensure proper aggregation of measurements through the whole taxonomy.
Keywords: IS specification language; internal quality; taxonomy; aggregation method